2016
DOI: 10.1016/j.biortech.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent production of carotenoids and lipid by a filamentous microalga Trentepohlia arborum

Abstract: h i g h l i g h t sT. arborum could simultaneously synthesize high amounts of carotenoids and lipid. Carotenoids (mainly b-carotene) accounted for ca. 5% in the microalgal lipid. First report of lipid and fatty acid accumulation characteristics in T. arborum. a r t i c l e i n f o t r a c tDuring the study of Trentepohlia arborum it became clear that its cells are rich in lipids and carotenoids. Thus, lipid content, composition and fatty acids profiles in individual lipid classes, as well as pigment profiles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The total chlorophyll (a and b) content and total carotenoid content were measured using the spectrophotometer methods of Chen et al (2015Chen et al ( , 2016 and Pompelli et al (2012), which were modified versions of the Wellburn method (1994). A sample of 10 mg of algae was incubated with 10 mL of DMSO and spun with a vortex, the Fisher Scientific Touch Mixer Model 232 (Fisher Scientific, United States).…”
Section: Chemicals and Solvents For Analysismentioning
confidence: 99%
“…The total chlorophyll (a and b) content and total carotenoid content were measured using the spectrophotometer methods of Chen et al (2015Chen et al ( , 2016 and Pompelli et al (2012), which were modified versions of the Wellburn method (1994). A sample of 10 mg of algae was incubated with 10 mL of DMSO and spun with a vortex, the Fisher Scientific Touch Mixer Model 232 (Fisher Scientific, United States).…”
Section: Chemicals and Solvents For Analysismentioning
confidence: 99%
“…Some stress conditions such as nutrient starvation, ultraviolet treatment, and high light levels have been found to affect the co‐production efficiency of lipids and β ‐carotene. Under conditions of nitrogen starvation, the lipid and carotenoid content increased by 55.4% and 53.0% in Trentpohlia arborum ; while, the lipid and carotenoid content increased by 24.3% and 44.6%, respectively when strains are exposed to high light levels 22 . Further exposed to the double stress conditions of nitrogen deficiency and high light (0 mmol/L ammonium and 150 μmol/m 2 s light), the lipid and carotenoid content increased by 55.2% and 117.2% by T. arborum compared to the original condition (18.7 mmol/L of ammonium and 35 μmol/m 2 s of light) 22 .…”
Section: Co‐production Of Lipids With Intracellular Productsmentioning
confidence: 95%
“…Under conditions of nitrogen starvation, the lipid and carotenoid content increased by 55.4% and 53.0% in Trentpohlia arborum ; while, the lipid and carotenoid content increased by 24.3% and 44.6%, respectively when strains are exposed to high light levels 22 . Further exposed to the double stress conditions of nitrogen deficiency and high light (0 mmol/L ammonium and 150 μmol/m 2 s light), the lipid and carotenoid content increased by 55.2% and 117.2% by T. arborum compared to the original condition (18.7 mmol/L of ammonium and 35 μmol/m 2 s of light) 22 . It was confirmed that nitrogen starvation could promote the conversion of membrane lipids into neutral lipids, which are more suitable for biodiesel accumulation, 33 and UV‐A (320–400 nm) is already known to induce β ‐carotene synthesis via a photo‐protecting reaction in microalgal cells 34 .…”
Section: Co‐production Of Lipids With Intracellular Productsmentioning
confidence: 95%
“…Stains of Nannochloropsis sp., Rhodotorula glutinis, and Neochloris oleoabundans have high contents of carotenoids. The red ketocarotenoid, astaxanthin (3, 30-dihydroxy-b,β-carotene 4,40-dione) is an antioxidant and the green microalga Haematococcus pluvialis is said to be a good natural source of astaxanthin [36][37][38][39][40].…”
Section: Carotenoidsmentioning
confidence: 99%